ANALISIS URGENSI PELATIHAN DALAM PENGEMBANGAN KOMPETENSI APARATUR SIPIL NEGARA (ASN) DI PENGADILAN NEGERI GUNUNGSITOLI - Lase, Yusnidar; Ndraha, Ayler Beniah (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract. This research investigates the imperative need for training in enhancing the competencies of Civil Servants (ASN) within the Gunungsitoli District Court. Competency development among ASN is a critical aspect of ensuring effective and efficient public service delivery. Through a comprehensive analysis, this study assesses the current competencies of ASN, identifies skill gaps, and evaluates the role of training programs in addressing these gaps. The research also explores the impact of competency development on organizational performance and service quality. Findings from this study are expected to inform policy recommendations for optimizing training initiatives and enhancing the overall capacity of ASN at the Gunungsitoli District Court.